Polar bears experience skeletal muscle atrophy in response to food deprivation and reduced activity in winter and summer - Whiteman, John P. (Conserv Physiol, 2017)
When reducing activity and using stored energy during seasonal food shortages, animals risk degradation of skeletal muscles, although some species avoid or minimize the resulting atrophy while experiencing these conditions during hibernation. Polar bears may be food deprived and relatively inactive during winter (when pregnant females hibernate and hunting success declines for other demographic groups) as well as summer (when sea ice retreats from key foraging habitats). We investigated muscle atrophy in samples of biceps femoris collected from free-ranging polar bears in the Southern Beaufort Sea (SBS) throughout their annual cycle. Atrophy was most pronounced in April–May as a result of food deprivation during the previous winter, with muscles exhibiting reduced protein concentration, increased water content, and lower creatine kinase mRNA. These animals increased feeding and activity in spring (when seal prey becomes more available), initiating a period of muscle recovery. During the following ice melt of late summer, ~30% of SBS bears abandon retreating sea ice for land; in August, these ‘shore’ bears exhibited no muscle atrophy, indicating that they had fully recovered from winter food deprivation. These individuals subsequently scavenged whale carcasses deposited by humans and by October, had retained good muscle condition. In contrast, ~70% of SBS bears follow the ice north in late summer, into deep water with less prey. These ‘ice’ bears fast; by October, they exhibited muscle protein loss and rapid changes in myosin heavy-chain isoforms in response to reduced activity. These findings indicate that, unlike other bears during winter hibernation, polar bears without food in summer cannot mitigate atrophy. Consequently, prolonged summer fasting resulting from climate change-induced ice loss creates a risk of greater muscle atrophy and reduced abilities to travel and hunt.